HGG-27. MALIGNANT TRANSFORMATION OF AN OPTIC NERVE GLIOMA: CASE REPORT. Issue 2 (22nd June 2018) - Erdemir, Huseyin; Erdemir, Gozde; Carlson, Aimee; Hsich, Gary; Tekautz, Tanya
Abstract: Optic pathway tumors are rare neoplasms of childhood with a 4-6% incidence of pediatric brain tumors. Optic pathway gliomas (OPG) consists of 65% of this small percentage. OPG is usually considered a low-grade lesions (WHO Grade I). In pediatric patients, malignant gliomas such as anaplastic astrocytoma or glioblastoma (GBM) of optic pathway are an exceedingly rare entity and present with aggressive clinical course. Malignant transformation from low-grade astrocytoma to anaplastic astrocytoma or GBM has been described in case series attributed to radiation therapy. Herein we report a fourteen-year old male patient with diagnosis of OPG which progressed to GBM nine years after the completion therapy. He was diagnosed at six-months of age and subsequently underwent four separate courses of chemotherapy initially with vincristine/carboplatin then vinblastine monotherapy, followed by vincristine/actinomycin-D and lastly vincristine/carboplatin via desensitization. Serial imaging studies did not demonstrate tumor progression for nine years after completing therapy. Almost fourteen years after the initial diagnosis, symptom-directed imaging studies showed progressive optic glioma. Bevacizumab monotherapy was started. The course complicated by thromboembolic stroke after the first dose of bevacizumab. Unfortunately he succumbed to the disease 5 weeks after initial hospitalization. Information obtained through autopsy reported disseminated GBM (WHO Grade IV) with extensive leptomeningeal spread. In this case-report, we review the patient's clinical course with imaging studies and molecular mechanism of malignant transformation. To our knowledge, this is the second case reporting malignant transformation of low grade OPG without any exposure to radiation therapy or underlying tumor predisposition.